Exploring the relationship between motor visual proficiency and performance metrics in elite skeet shooters: An in-depth analysis - Dongxu Gao; Beishi Hu; Tinggang Yuan; Qingshou Guo; Pengfei Wei; Yang Wu; Chao Chen (PLoS ONE, 2025)
Background Motor vision ability entails using eyesight to collect and interpret information, such as tracking moving targets, understanding spatial relationships, predicting object movement, making decisions, and taking actions. This study aimed to explore the relationship between the visual skills of elite skeet shooters and their competition performance. Methods In this cross-sectional study (n = 42), elite skeet shooters from the Chinese National Clay Target Shooting Training Team with a mean age of 25.63 ± 6.2 years and an average training years of 7.64 ± 3.43 participated. The fundamental visual ability variables were measured using the Senaptec system, and their specialized visual ability indices were measured during target viewing tasks using aSee Glasses. The relationship between visual acuity test indices and sports performance was analyzed using correlation coefficients and multiple linear regression analysis. Results The strongest positive association was observed between Perceived Range (PS) and sports performance (r = 0.486, p < 0.001), indicating that athletes with a higher perceptual range tend to perform better. Moderate positive correlations (r = 0.333 to r = 0.362, p < 0.001) were also found for Visual Clarity (VCR), Near/Far Switching (NFQSCORE), Multi-target Tracking Speed (MOTSPEED), and Go/No-Go Score (GNGSCORE), suggesting these visual skills are beneficial for performance. Conversely, a strong negative correlation was noted between Near/Far Switching Reaction Time (NFQFRT) and performance (r = −0.510, p < 0.001), highlighting that slower reaction times are detrimental. Additionally, Target Capture (TC), Depth Perception (DPP), and Eye-Hand Coordination (EHC_RT) showed moderate negative correlations (r = −0.425 to r = −0.241, p < 0.001) with performance. The regression model explained 76.7% of the variance in athletes’ specialized performance (R² = 0.752, F = 49.692, p < 0.001), with key predictors including NFQFRT, EHC_RT, PS, and several specialized visual skills. Conclusion The visual abilities of elite skeet shooters significantly affect their performance, underscoring the importance of perceptual range, reaction time, and specialized visual skills.